Treatment of chronic myeloid leukemia when imatinib fails - Hehlmann, Rüdiger; Jung-Munkwitz, Susanne; Saußele, Susanne (Expert opinion on pharmacotherapy, 2011)
Introduction: Imatinib failure represents a major clinical challenge in the management of chronic myeloid leukemia. Areas covered: Definition of failure, its causes, the various approaches to the treatment of imatinib failure such as imatinib dose escalation, second-generation tyrosine kinase inhibitors and stem cell transplantation, and monitoring of residual disease are covered in this review. Selected investigational agents and the management of blast crisis are also reviewed. After reading the review the reader will understand how to manage imatinib failure. Expert opinion: Imatinib failure can be managed in most cases by a careful appraisal of its causes and a rational selection of treatment options.
Gesehen am 28.09.2022